MODERN TECHNOLOGIES IN THE STUDY, PRESERVATION AND MANAGEMENT OF CULTURAL HERITAGE: MODERN TECHNOLOGIES IN THE STUDY, PRESERVATION AND MANAGEMENT OF CULTURAL HERITAGE - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The new technologies, which will be briefly described below, provide opportunities for documenting cultural and historical structures as a whole and individual details with absolute accuracy and credibility, completely eliminating the subjective factor, speed, representativeness, usability in design.